2017
DOI: 10.3389/fcomm.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Identifying Specific Language Impairment in Bilingual Populations in Germany

Abstract: This study investigates the performance of 22 monolingual and 54 bilingual children with and without specific language impairment (SLI), in a non-word repetition task (NWRT) and a sentence repetition task (SRT). Both tasks were constructed according to the principles for LITMUS tools (Language Impairment Testing in Multilingual Settings) developed within COST Action IS0804 and incorporated phonological or syntactic structures that are lin guistically complex and have been shown to be difficult for children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 57 publications
3
45
0
4
Order By: Relevance
“…, Armon‐Lotem and Meir , Boerma et al . , Chiat and Polišenská , Hamann and Abed Ibrahim , Marinis et al . ), and are encouraging in that they have shown fair to excellent diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Armon‐Lotem and Meir , Boerma et al . , Chiat and Polišenská , Hamann and Abed Ibrahim , Marinis et al . ), and are encouraging in that they have shown fair to excellent diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative coding procedure was also used, target structure , for whether the sentence preserves the syntactic construction targeted, which disregards repetition errors that do not affect the structure of the stimulus sentences (e.g., lexical errors) (Fleckstein et al . ; Abed Ibrahim and Hamann ; Hamann and Abed Ibrahim ).…”
mentioning
confidence: 99%
“…Not to mention that evaluation in two languages is time-consuming and that some of the immigrant L1 varieties undergo language change as a result of contact with the majority/societal language (L2), e.g., Immigrant Turkish in Germany (see Schroeder and Dollnick, 2013; Chilla and Şan, 2017). Hamann and Abed Ibrahim (2017) showed that even when dominance-adjusted bilingual cut-off criteria (Thordardottir, 2015) were applied to the standardized L1 tests, more than a quarter of the L1-dominant children in their sample were classified as SLI by the L1-tests. The fact that the latter children performed within aged-expectations on the L2-tests albeit being dominant in their heritage language questions the applicability of L1 tests in heritage contexts (even with norm adjustments) and suggests that direct assessment measures in the L2 are more reliable for identifying LI in bilingual populations, especially in case of heritage language speakers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that SRTs eliciting structures involving the latter operations can be reliably used to tease apart typically developing bilingual children from monolingual and bilingual children with SLI, not only in bilingual but also in bialectal settings (e.g., Armon-Lotem and Meir, 2016; Meir et al, 2016, 2017 for LITMUS-SRT in Russian and Hebrew; de Almeida et al, 2017; Fleckstein et al, 2018 for French; Lein et al, 2016; Abed Ibrahim and Hamann, 2017; Hamann et al, 2017; Hamann and Abed Ibrahim, 2017 for German; Theodorou et al (2017) for Cypriot-Greek; see also Marinis et al, 2017 for an overview). In particular, Armon-Lotem and Meir (2016) showed that although the highest level of diagnostic accuracy can be achieved using a combination of SRTs in the child’s L1/Russian and L2/Hebrew (applying bilingual cut-offs), good diagnostic accuracy can still be achieved if SRT is only administered in the societal language (L2-Hebrew).…”
Section: Introductionmentioning
confidence: 99%
“…[16]. Besonders wichtig ist die Erkenntnis, dass die Testergebnisse des NWRT nur bedingt von der Sprachdominanz beeinflusst werden, sodass Kinder, die in ihrer nicht dominanten Sprache Deutsch getestet werden, nicht stärker benachteiligt werden als Kinder, bei denen Deutsch die dominante Sprache ist [17].…”
Section: Lernzielunclassified